Kegalauan Identitas dan Kekerasan Sosial: Multikulturalisme, Demokrasi dan Pancasila - Azra, Azyumardi (Social Welfare Study Program, 2012)
Turmoil identity became one of the most obvious symptoms of Indonesian community in the Post-Soeharto Era. The roots of the turmoil of identity is not only related to changes in political, social, economic, cultural and religious locally internally, but also with the expansion and penetration of the change and globalization. The emergence of social violence, loss of patience, social temper, the decline of respect and obedience to the law, ethics and morals, as well as the nuances of ethnic and religious conﬂ ict showed persistent social crisis that followed the disorientation of cultural identity. Keywords: kegalauan identitas, krisis identitas, kekerasan sosial, multikulturalisme, demokrasi, rejuvenasi Pancasila, bhinneka tunggal ika.